The Effect of Investment Policy, Dividend Policy, and Profitability on Firm Value with Firm Size as a Moderating Variable in the Banking Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the Period 2021–2023 - Naomi Kezia; Viola Caroline Br. Samosir; Sabrina Fricilya Juwita Tampubolon; Sulia Sulia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the influence of investment policy, dividend policy, and profitability on firm value, using firm size as a moderating variable in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The research employs a quantitative approach with data gathered from 16 banks, yielding 48 observations. Analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The findings show that investment policy and profitability have a positive and significant effect on firm value, while dividend policy exerts a positive but not statistically significant influence. Firm size significantly moderates the relationship between investment policy and profitability with firm value, indicating its amplifying role in enhancing these effects. However, firm size does not moderate the influence of dividend policy. These results highlight the importance of strategic investment and profitability management in increasing firm value, particularly in larger firms with more resources. The study contributes both theoretically and practically by offering insights into how internal financial decisions interact with firm characteristics in shaping company valuation. It also provides a relevant framework for financial managers and investors in the post-pandemic recovery phase. This research supports data-driven strategies to enhance long-term competitiveness and market confidence.